(untitled) (Praxis Educativa, 2023)
This research purpose was to describe institutional suggestions and exigences about the use of technologies in a local University institutional documents. Content analysis of twelve documentary sources and four interviews were made. Eight keywords were selected. Presence of each word in relation to suggestions about the digital technology use were analyzed, among which Distance Education (DE) proposals; approval of the SIED, its modifications and reorganization; the teaching schedule in the virtual campus; and hybrid pedagogical models. In the interviews, the creation of the SIED, the impact of the pandemic to the virtualization process and the instances of evaluation in the DE were the highlighted aspects. Expectations were expressed regarding the use of digital technologies when the pandemic is over and considered the inclusion of hybrid instances in university degree courses.